Suicidal ideation in bully victimized school children and adolescents:a meta analysis (Bangladesh Journal of Psychiatry, 2017)
In the recent years there has been increased attention to the association of bullying involvement and suicidal ideation in school going children and adolescents. This meta analytic study was conducted by online searching of articles using Pub Med data bases and Google scholar. Total 21 both USA based and non USA based studies were included and sample size were 219,929. We used the research term bullying, suicide, children, adolescence , school bullying , suicidal ideation and by using the term cross sectional studies, from 2010 to 2013 for studies identification. One predictor bully victimization and one outcome suicidal ideation were analyzed. Inverse weighted average was measured to see the effect size and forest plot was applied for data presentation. All the steps of meta analysis were followed. Our pooled data showed increase risk of suicidal ideation in bully victim.The results showed that odd ratio of suicidal ideation was 2.18 in bully victims in USA based studies and 95% CI 2.12 to 2.24 and odds ratio of non USA based studies was 2.31 and 95% CI 1.73 to 3.09 whereas combined USA and non USA studies odd ratio was 2.6 and 95% CI 2.20 to 3.22. Findings concluded that bully victims had the increased risk of suicidal ideation.Bang J Psychiatry June 2015; 29(1): 35-40